2019
DOI: 10.1111/1471-0528.15658
|View full text |Cite
|
Sign up to set email alerts
|

STRIDER NZAus: a multicentre randomised controlled trial of sildenafil therapy in early‐onset fetal growth restriction

Abstract: Objective To assess the effect of maternal sildenafil therapy on fetal growth in pregnancies with early-onset fetal growth restriction.Design A randomised placebo-controlled trial.Setting Thirteen maternal-fetal medicine units across New Zealand and Australia.Population Women with singleton pregnancies affected by fetal growth restriction at 22 +0 to 29 +6 weeks.Methods Women were randomised to oral administration of 25 mg sildenafil citrate or visually matching placebo three times daily until 32 +0 weeks, bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 27 publications
2
76
1
1
Order By: Relevance
“…Moreover, no positive effects on the primary, secondary, or exploratory outcomes, as defined in the statistical analysis plan, 38 were seen. The results of the recently published STRIDER UK trial 39 as well as the (at that time unpublished) data of the STRIDER New Zealand/Australia trial 40 were included in the DSMB deliberations, as was foreseen in the DSMB…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no positive effects on the primary, secondary, or exploratory outcomes, as defined in the statistical analysis plan, 38 were seen. The results of the recently published STRIDER UK trial 39 as well as the (at that time unpublished) data of the STRIDER New Zealand/Australia trial 40 were included in the DSMB deliberations, as was foreseen in the DSMB…”
Section: Resultsmentioning
confidence: 99%
“…Our present finding of an increased incidence of pulmonary hypertension after antenatal sildenafil administration was not observed in the 2 other STRIDER trials. 39,40 This difference may be explained by definition differences, diagnostic strategies, or thresholds of suspicion. Our finding may indicate an important safety signal, and causality is a possibility because sildenafil targets the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Table A,B (see Supplementary material) shows the judgment of risk of bias of the individual studies. Two of the 5 included randomized controlled trials (RCT) were judged as “unknown” risk of bias. This judgment was mostly based on the fact that these studies were retrospectively registered and not blinded, and that some of the baseline criteria and outcomes were not reported for pregnancies that involved neonatal death.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials of maternal treatment with the vasodilator Sildenafil have shown either no improvement in fetal outcome measures (Groom et al . ; Sharp et al . ) or in the case of the Dutch trial, have been halted due to an increased risk of poor fetal outcomes (Groom et al .…”
Section: Discussionmentioning
confidence: 99%
“…Improving fetal substrate supply has been previously attempted in IUGR pregnancies. Clinical trials of maternal treatment with the vasodilator Sildenafil have shown either no improvement in fetal outcome measures (Groom et al 2019;Sharp et al 2019) or in the case of the Dutch trial, have been halted due to an increased risk of poor fetal outcomes (Groom et al 2018). However, before commencement of these human trials, Sildenafil treatment in a sheep model of IUGR was found to be detrimental to uteroplacental perfusion and fetal wellbeing (Miller et al 2009).…”
Section: Discussionmentioning
confidence: 99%